2018
DOI: 10.7150/ijms.21856
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MED12 Mutation in Multiple Uterine Leiomyomas in South Korean patients

Abstract: Uterine leiomyomas are one of the most common benign gynecologic tumors, but the exact causes are not completely understood. In 2011, through DNA sequencing, MED12 mutation was discovered in approximately 71% of uterine leiomyomas. Several recent studies confirmed the high frequency of MED12 mutation in uterine leiomyoma. Nevertheless, no study has been done on MED12 mutation in the case of patients with multiple leiomyomas in a patient. The purpose of this study was to investigate the frequency of MED12 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…All MED12 gene mutations were located within exon 2 and, most probably, they presented the strongest association with UF development [18]. Various studies were conducted in the following years and confirmed these observations [19,20].…”
Section: Biology Of Uterine Fibroids: Overviewmentioning
confidence: 77%
“…All MED12 gene mutations were located within exon 2 and, most probably, they presented the strongest association with UF development [18]. Various studies were conducted in the following years and confirmed these observations [19,20].…”
Section: Biology Of Uterine Fibroids: Overviewmentioning
confidence: 77%
“…Moreover, the adjacent tissue of different cancer tumors presented a unique intermediate state between healthy and tumor [ 14 ]. To test our hypothesis, we compared the transcriptome of myometrial samples from non-fibroid patients, with samples from fibroids with the most common fibroid subtype, MED12 mt [ 17 ], and their matching “normal” myometrium and showed that, although the two tissues are clearly more alike than not when compared to fibroid tissues, there is a distinct phenotype for each.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some histopathological characteristics of leiomyosarcomas such as mitotically active cells have also appeared in leiomyoma cases with MED12 mutations, indicating possible transformation of leiomyoma toward malignancy when somatic mutations are accumulated. MED12 mutations are reported not just in benign uterine neoplasms but also in highly aggressive leiomyosarcomas (Markowski et al, 2012; Mäkinen et al, 2014b; Sadeghi et al, 2016; Yoon et al, 2017; Lee et al, 2018). Moreover elevated number of mitoses in leiomyomas may also result from hormonal factors, because these tumors frequently occur in pregnancy, during the secretory phase of the menstrual cycle, and in patients undergoing hormonal therapy (Walker, 2002; Wise et al, 2004; Salama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Variety of MED12 mutations including missense, in-frame insertion-deletions, and intrinsic type variations were found in different leiomyoma phenotypes (Mäkinen et al, 2011a,b, 2014a; Halder et al, 2014; Osinovskaya et al, 2016; Sadeghi et al, 2016; Heinonen et al, 2017; Wang et al, 2017). It is of particular interest, to note that all reported mutations were mostly localized to exon 2, underlining its potential contribution in the genesis of uterine leiomyomas (Barbieri et al, 2012; Mäkinen et al, 2013; Schwetye et al, 2014; Osinovskaya et al, 2016; Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%